Effects of Carica papaya leaf extract on platelet recovery in dengue fever - I Made Lingga Tresnadinata; Made Bayu Permasutha; Ni Nyoman Mestri Agustini; Komang Della Pramita Putri; Jerroll Septian Tammubua; Made Ayu Rahayu Agastyane Rahmadewi; Made Devina Febryanti; Ni Putu Cempaka Pradnyadewi (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Dengue infection is a major global health threat, often manifesting as thrombocytopenia. While Carica papaya is traditionally used to enhance platelet counts, synthesized clinical evidence regarding its efficacy remains limited. This study evaluated the effectiveness of Carica papaya leaf extract (CPLE) on platelet count recovery in adult dengue patients. Following PRISMA 2020 guidelines, a systematic literature search was conducted across two databases (PubMed and Google Scholar) to identify randomized controlled trials (RCTs) published between 2012 and 2024. Risk of bias was assessed using Cochrane RoB 2, and data were analyzed in R Studio using a random-effects model. Four RCTs involving 279 adult participants were included. The meta-analysis demonstrated that CPLE significantly increased platelet counts compared to controls, with a pooled mean difference of 14.34 × 10³/µL (95% CI: 5.90 to 22.77; p = 0.0124 for overall effect). Statistical heterogeneity was low-to-moderate (I2 = 27.0%), indicating a generally consistent therapeutic direction. In conclusion, CPLE serves as a viable adjunctive therapy for accelerating platelet recovery in adult dengue patients. However, given the sensitivity of the pooled estimates to specific highly weighted trials, future large-scale, rigorously blinded RCTs are needed to solidify these findings and confidently support their integration into clinical management protocols.Keywords: Carica papaya; dengue fever; thrombocytopenia; platelet recovery; meta-analysis; adjucntive therapy